Incidence and cumulative incidence as supplemental measures of the scale of imprisonment - Rhodes, William (Crime & delinquency, 2018)
Prison growth has primarily been measured as a prevalence over time. We propose cohort-specific supplemental measures: incidence based on the age of first adult admission into prison, and cumulative incidence, based on the proportion of people who will be imprisoned during their lifetime. We present a new estimation method using administrative data. Prior research derived estimates from inmate surveys. The main advantages of this new method are that estimates can be updated every year with little cost and minimal imputation. We present results showing that we have likely reached an inflection point in the growth of cumulative incidence, and the ratio between Blacks and Whites is declining although the disparity is still large—roughly 4.5 to 1.